Workload, work motivation, and job satisfaction as predictors of nurses’ performance quality in a regional public hospital: A cross-sectional study - Herwin Herry Supardjo; Julia Fitrianingsih; Dian Meiliani Yulis (Jurnal Edukasi Ilmiah Kesehatan, 2026)
Introduction: Nurses’ performance is a key determinant of hospital service quality, patient safety, and continuity of care. In regional hospitals, an imbalance between workload, motivation, and job satisfaction may affect the quality of nursing performance. This study aimed to analyse the influence of workload, work motivation, and job satisfaction on nurses’ performance quality at Mamuju Tengah Regional Public Hospital in Indonesia. Research Methodology: This study employed a quantitative analytic design with a cross-sectional approach. A total of 103 nurses were selected using purposive sampling. Data were collected through structured questionnaires measuring workload, work motivation, job satisfaction, and nurses’ performance quality. Bivariate analysis was performed using the Chi-Square test, and multivariate analysis was conducted using ordinal logistic regression at α = 0.05. Results: Workload was not significantly associated with nurses’ performance quality (p = 0.410). In contrast, work motivation and job satisfaction showed significant effects on nurses’ performance quality (p < 0.001 and p < 0.05, respectively). Ordinal logistic regression indicated that work motivation and job satisfaction remained significant predictors of nurses’ performance quality. Moderate work motivation had an estimated coefficient of β = −2.930 (p = 0.001), while high work motivation had a coefficient of β = −2.779 (p < 0.001). Moderate job satisfaction showed β = −3.520 (p = 0.004), and high job satisfaction showed β = −2.697 (p = 0.022). The model demonstrated acceptable explanatory power, with a Nagelkerke R² of 0.466. Conclusion: Work motivation and job satisfaction were the most influential factors associated with nurses’ performance quality. Hospital management should strengthen motivational strategies, fair reward systems, career development, and supportive work environments to improve nursing performance and sustain healthcare service quality.